Respuesta :
y = 4x + 11
y = -2x - 1
4x + 11 = -2x - 1
4x + 2x = -1 - 11
6x = -12
x = -12/6
x = -2
y = 4x + 11
y = 4(-2) + 11
y = -8 + 11
y=3
A. (-2,3)
y = -2x - 1
4x + 11 = -2x - 1
4x + 2x = -1 - 11
6x = -12
x = -12/6
x = -2
y = 4x + 11
y = 4(-2) + 11
y = -8 + 11
y=3
A. (-2,3)
Answer:
Option A. (-2, 3)
Step-by-step explanation:
The given equations graphed are Y = 4x + 11 and Y = -2x - 1
Now for the solution to the system of equations graphed Y values will be the same or a point where these lines intersect will be the solution.
Y = 4x + 11 = -2x - 1
4x + 2x = -1 - 11
6x = -12
x = -2
Now by putting x = -2 in the first equation.
Y = 4.(-2) + 11 = -8 + 11 = 3
The common point will be (-2, 3)
Therefore option A. (-2, 3) will be the answer.